Comparison of neonatal outcome parameters between thick and thin meconium stained liquor: a prospective study - K., Rupa Vani; Pati, Banishree; K. S., Veena; V. R., Hemanth Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Meconium stained liquor is a commonly observed phenomenon in the day-to-day obstetric practice, the incidence being 12-22%. Meconium stained liquor can be considered as a normal physiological event in a term fetus in the absence of fetal heart rate abnormalities. It has greater significance as one of the parameters of fetal distress, when associated with abnormal fetal heart rate pattern. The aim of the present study was to study the association of, fetal heart rate abnormalities, mode of delivery and neonatal outcome with different grades of meconium stained liquor. Methods: A prospective study was conducted in one hundred and fifty cases of meconium stained liquor beyond 37 weeks gestation admitted to the labor room in a tertiary care Centre. Depending on the consistency of meconium, the patients were divided into two groups namely, Thick meconium stained liquor (group K) and Thin meconium stained liquor (group N). Maternal conditions, Intrapartum fetal heart rate pattern, Apgar scores and neonatal morbidities were studied in relation to the grade of meconium. The proportions between the two groups were compared using chi-square test and Fisher’s exact t-test. Results: The incidence of post term pregnancy (p=0.004), unbooked (p=0.007) status and oligohydramnios (p=0.01) were significantly higher among group K when compared to group N. Non-reassuring fetal heart rate pattern (p=0.002) and Apgar score ≤7 (p=0.02) were significantly higher in group K. In group K, non-reassuring fetal heart rate pattern and reduced beat to beat variability were significantly associated with low Apgar score (p=0.01). Conclusions: Neonatal outcomes like low Apgar score, meconium aspiration syndrome are strongly associated with thick meconium stained liquor. Visual grading of liquor into thick and thin meconium stained may help in timely obstetric intervention leading to a better neonatal outcome.